Tim Rogan. The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. - Dale, Gareth (The American Historical Review, 2019)
When the capitalist system hits the rocks and neoclassical economics loses its aura, alternative traditions invite attention. Tim Rogan’s The Moral Economists i
Keywords: The Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson, and the Critique of Capitalism (book); book review; capitalism

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
Keywords: Great Transformation, The (Book); KING, Martin Luther; Poor People's Campaign; TRUMP, Donald; embeddedness

In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
Keywords: Human rights; Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); Rogan, Tim; austerity (economics); book review; cultural history; nonfiction

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI, Karl, 1886-1964 - political & social views; ROGAN, Tim; TAWNEY, R. H. (Richard Henry), 1880-1962; THOMPSON, E. P. (Edward Palmer), 1924-1993; book review; nonfiction; political attitudes

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
Keywords: Japan; Tokugawa Period, Japan, 1600-1868; capitalism; double movement; history; landlord-tenant relations

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate

"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought -- from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp -- than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view -- that is, to a radical approach to Polanyi's thought.
Keywords: Poor Law; WEBER, Max, 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Markets, Knowledge and Human Nature: Friedrich Hayek, Karl Polanyi and Twentieth-century Debates on Modern Social Order - Innset, Ola (European History Quarterly, 2017)
The article reads the works of Friedrich Hayek (1899-1992) and Karl Polanyi (1886-1964) in the light of their political commitments to neoliberalism and socialism respectively. It argues that both thinkers were inspired to explain history and recent events in line with these commitments in their 1944 publications, The Road to Serfdom and The Great Transformation. Furthermore, they both developed their most significant insights by attempting to counter perceived challenges from political projects to which they were opposed. Polanyi spent much of his life trying to disprove a liberal attack on socialism as out of touch with the realities of human nature, whereas it was in debates with socialists that Hayek developed a new theory of the epistemological functioning of markets, which then became foundational for the neoliberal project. Taking into account the high-stakes politics of Vienna in the interwar years is crucial for fully understanding the social theory of these two thinkers.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; human behavior; knowledge; markets; neoliberalism; social order; socialist accounting; socialist calculation debate; totalitarianism

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Karl Polanyi: A Life on the Left - Innset, Ola (European History Quarterly, 2017)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); nonfiction

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS, Bernie; TRUMP, Donald

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism--R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
Keywords: HENRY, Richard; PALMER, Edward; TAWNEY, R.H.; THOMPSON, E.P.; capitalism; moral and ethical aspects; moral economy; socialism

Karl Polanyi and the Reality of Society - Behrent, Michael C. (History and Theory, 2016)
This essay reconsiders Karl Polanyi's famous thesis about the “embeddedness” of the economy through an examination of two recent books: For a New West, a collection of previously unavailable essays by Polanyi, and Fred Block and Margaret R. Somers's The Power of Market Fundamentalism: Karl Polanyi's Critique. The guiding thread of this analysis is the claim that a constant in Polanyi's thought was his belief in what he called “the reality of society,” that is, that society exists as a social fact over and above the individuals that constitute it. The essay begins by tracing Polanyi's intellectual development, drawing primarily on the essays found in For a New West. Polanyi's quest to reconcile individual freedom with social solidarity led him first, in the years between the First and Second World Wars, to embrace liberal socialism, before his readings in anthropology persuaded him that traditional economies “embed” the economy in social relations and that the nineteenth-century liberal project of a “disembedded” economy (through the so-called free market) is a departure from this anthropological norm. The essay then examines and questions Block and Somers's claim that Polanyi maintained that the economy is always “already embedded,” arguing notably that Polanyi believed that the advent of market society entailed an economy that was actually disembedded from social relations, not merely one that was re-embedded in an alternative set of institutions.
Keywords: already embedded; anthropology; capitalism; embeddedness; liberalism; markets; reality of society; socialism; society

Embedding Capital: Political-Economic History, the United States, and the World - Kramer, Paul A. (Journal of the Gilded Age & Progressive Era, 2016)
The article examines U.S. political and economical history in the context of its impact as well as influence to world affairs. Topics discussed include the Marxist's historical approaches to analysis of capital as in Karl Polanyi's take on American capitalism, "primitive accumulation" with regimes of commodification and the "new history of capitalism" hype. Also mentioned were transnational expansion of humanitarianism, international education sponsorship and Andrew Carnegie's philanthropy.
Keywords: United States - politics & government - history; capital; capitalism; economics - United States - history; embeddedness; humanitarianism

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA, Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU, Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Keywords: archaeology; business & economics; economic history; history / ancient / general

Port of trade - Möller, Astrid (The Encyclopedia of Ancient History, 2013)
A “port of trade” is a theoretical concept developed by Karl Polanyi (1886–1964) to describe the phenomenon of a particular kind of trading post.
Keywords: anthropology; economic history; multiculturalism

Nature and Power - Radkau, Joachim (Social Science History, 2013)
Nature and Power is to be understood not only as human power against nature but also as power by nature in the sense of Michel Foucault's biopouvoir (biopower) or Francis Bacon's "Naturae non imperator nisiparendo" (Only by obeying nature may we dominate nature). The fragile human attempts to get power over nature and by nature have a long history, reaching back over millennia until prehistoric times, and much of world history may be explained in part by the unstable relationship between humans and nature. The environmental approach offers afresh look at global history. The great change that has happened in modern times seems to have been described best by Karl Polanyi (1944) in his Great Transformation, which also refers to a revolution in the human relation to nature. There are primeval symbioses of humans and nature that are the basis of environmental history until modern time. A global history of the environment may be written for a long time along the three great commons of history: woodlands, water, and pasture. The dark tune of Garrett Hardin's (1968) "Tragedy of the Commons," to be sure, does not dominate the whole melody of environmental history. There is also a lot of historical evidence for Elinor Ostrom's rehabilitation of the commons. But it is better to be cautious with dogmatic theories and sweeping judgments. In modern times Hardin may be right, at least in this or that regard. Ostrom's concept applies only to local, not to global commons. The underlying philosophy of Nature and Power is neither optimism nor pessimism but possibilism.
Keywords: BACON, Francis, 1561-1626; FOUCAULT, Michel, 1926-1984; Nature & Power: A Global History of the Environment (Book); POLANYI, Karl, 1886-1964; RADKAU, Joachim; environmental history; environmentalism; nature and civilization

Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Keywords: MALTHUS, T. R.; SMITH, Adam, 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Conventions, the Great Transformation and Actor Network Theory - De Munck, Bert (Konventionen, die große Transformation und Actor Network Theory., 2012)
This article proceeds from the field of tension between the synchronical approach of the economics of convention and the diachronical approach of economic anthropology (in the tradition of Karl Polanyi). It is argued that the economics of convention remain problematic to historians in that they fail to capture the long term transformations traditionally referred to as the emergence of modernity and the coming about of homo economicus. As a possible solution, the use of concepts and insights from Actor Network Theory is proposed. While this cluster of theories enables an historical perspective without considering modernity as a natural process, it confronts changing relationships between subjects, objects and cultural systems of meaning head on.
Keywords: CALLON, Michel; actor-network theory; conventions; economic anthropology; economic aspects; history; manners & customs; modernity; performativity

Twentieth-Century Jewish Émigrés and Medieval European Economic History - Mell, Julie (Religions, 2012)
This essay discusses the intellectual contributions of five Jewish émigrés to the study of European economic history. In the midst of the war years, these intellectuals reconceptualized premodern European economic history and established the predominant postwar paradigms. The émigrés form three distinct groups defined by Jewish identity and by professional identity. The first two (Guido Kisch and Toni Oelsner) identified as Jews and worked as Jewish historians. The second two (Michal Postan and Robert Lopez) identified as Jews, but worked as European historians. The last (Karl Polanyi) was Jewish only by origin, identified as a Christian socialist, and worked first as an economic journalist, then in worker's education and late in life as a professor of economics. All five dealt with the origin of European capitalism, but in different veins: Kisch celebrated and Oelsner contested a hegemonic academic discourse that linked the birth of capitalism to Jews. Postan and Lopez contested the flip-side of this discourse, the presumption that medieval Europe was pre-capitalist par excellence. In doing so, they helped construct the current paradigm of a high medieval commercial revolution. Polanyi contested historical narratives that described the Free Market as the natural growth of economic life. This essay explores the grounding of these paradigms in the shared crucible of war and exile as Jewish émigrés. This shared context helps illuminate the significance of their intellectual contributions by uncovering the webs of meaning in which their work was suspended.
Keywords: Europe; European economic history; Jewish émigrés; KISCH, Guido; LOPEZ, Robert; OELSNER, Toni; POSTAN, Michael; biographical; economic history; historical literature; identity (philosophical concept); immigrants; intellectuals; medieval economic history; research

The peaceful conspiracy: bond markets and international relations during the Pax Britannica - Flandreau, Marc; Flores, Juan H. (International Organization, 2012)
This article provides foundations to K. Polanyi's famed argument that monopoly power in the global capital market served as an instrument of peace during the Pax Britannica (1815-1914). We focus on the role of intermediaries and certification. We show that when information and enforcement are imperfect, there is scope for the endogenous emergence of 'prestigious' intermediaries who enjoy a monopoly position and as a result, control government actions. They can implement conditional lending: they subject the distribution of credit to the adoption of peaceful policies. Prestigious intermediaries act that way because of their concern with maintaining an unblemished track record when wars increased risks of default. Our analysis, which brings together insights from different disciplines, provides a significant extension to, and departure from, recent research on how countries accumulate reputational capital.
Keywords: Pax-Britannica; United Kingdom; bond markets; economic history; global capital market (1815-1914); international relations

Embedding Markets in Temporal Structures: A Challenge to Economic Sociology and History - Eisenberg, Christiane (Die Einbettung von Märkten in temporalen Strukturen: Eine Herausforderung für Wirtschaftssoziologie und Geschichte., 2011)
The essay examines from a historian's point of view the approaches to the analysis of market exchange in new economic sociology and explores in which way sociology and history can cooperate in embedding markets in temporal structures. In a first step the author sharply criticises the favourable reception given to Karl Polanyi's work "The Great Transformation" in the field of new economic sociology. In particular she discusses the narrowing of research perspectives and its negative side effects on the sociology of markets. There then follows a second step: in order to find a linking point for interdisciplinary cooperation, beginning with the current state of historical research, the author makes several considerations on the significance of temporal structures and the time factor in general in analysing markets and market societies.
Keywords: Continental Europe; England; Great Britain; economic history; economic sociology; history - methodology; interdisciplinary approach to knowledge; interdisciplinary research; longue durée; market society; socioeconomics; time structures

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

From Menger to Polanyi: The Institutional Way - Cangiani, Michele (Austrian Economics in Transition, 2010)
The crisis of the institutions of liberal capitalism dates back to the last decades of the nineteenth century. Economics was thenceforth forced to radically reconsider its achievements and even its basic presuppositions, to the extent that they were linked to a free-market and perfect-competition model.
Keywords: economic history; economic systems; economic theory; financial economics; history of economic thought; international economics; macroeconomics; mathematical methods; methodology; monetary economics; quantitative economics

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
Keywords: classical Greek economy; economic history; embeddedness

Polanyi in the United States: Peter Drucker, Karl Polanyi, and the Midcentury Critique of Economic Society - Immerwahr, Daniel (Journal of the History of Ideas, 2009)
Abstract:This essay explores the connections between Karl Polanyi's The Great Transformation (1944) and midcentury social theory in the United States. It argues that Polanyi shared with his U.S. colleagues a critique of market society. In particular, Polanyi's work bears close resemblance to the early thought of management theorist Peter Drucker, with whom Polanyi lived while writing his celebrated book. By comparing Polanyi to his contemporaries who advanced similar ideas, one gains a clearer sense of the particularities of Polanyi's project and of the fairly widespread movement in the United States to reject economistic thinking.
Keywords: DRUCKER, Peter; history; social theory

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
Keywords: biography; essence of fascism

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Karl Polanyi for Historians: An Alternative Economic Narrative - Knowles, Rob; Owen, John R. (The European Legacy, 2008)
The purpose of this essay is to provide the historian with a generic understanding of the term economy by examining some aspects of the work of the Hungarian “economic historian” Karl Polanyi (1886–1964). It does not seek to explain Polanyi's economic ideas to economists nor does it seek to locate his ideas within the discourses of the academic discipline of economics; there is abundant academic literature which carries out those tasks. This essay is intended to help fill a void in the historical understanding, especially the modern historical understanding, of the term economy, and of how the characteristics associated with it are generally understood. Yet, in reality, it is the neoclassical paradigm of economics which is typically and uncritically taken to be the touchstone for understanding the economy. This circumstance is problematic, however, when referring to the economy of societies earlier than the late nineteenth century or of societies whose culture differs radically from that of the advanced capitalist “west.” Polanyi's insights may help historians avoid the risk of either distorting or anachronistically misunderstanding the economy of such societies.
Keywords: economic history; economic theory; history

Weber, Polanyi, and Finley - Tompkins, Daniel P. (History and Theory, 2008)
KM: a review article on Nafissi's book.
Keywords: WEBER, Max, 1864-1920; biography; review

Third Ways: How Bulgarian Greens, Swedish Housewives, and Beer-swilling Englishmen Created Family-centered Economies-- and why They Disappeared - Carlson, Allan C. (ISI Books, 2007)
Freewheeling capitalism or collectivist communism: when it came to political-economic systems, did the twentieth century present any other choice? Does our century? In Third Ways, social historian Allan Carlson tells the story of how different thinkers from Bulgaria to Great Britain created economic systems during the twentieth century that were by intent neither capitalist nor communist. Unlike fascists, these seekers were committed to democracy and pluralism. Unlike liberal capitalists, they refused to treat human labor and relationships as commodities like any other. And unlike communists, they strongly defended private property and the dignity of persons and families. Instead, the builders of these alternative economic systems wanted to protect and renew the “natural” communities of family, village, neighborhood, and parish. They treasured rural culture and family farming and defended traditional sex roles and vital home economies. Carlson's book takes a fresh look at distributism, the controversial economic project of Hilaire Belloc and G. K. Chesterton which focused on broad property ownership and small-scale production; recovers the forgotten thought of Alexander Chayanov, a Russian economist who put forth a theory of “the natural family economy”; discusses the remarkable “third way” policies of peasant-led governments in post–World War I Bulgaria, Poland, and Romania; recounts the dramatic and largely unknown effort by Swedish housewives to defend their homes against radical feminism; relates the iconoclastic ideas of economic historian Karl Polanyi, including his concepts of “the economy without markets” and “the great transformation”; and praises the efforts by European Christian Democrats to build a moral economy on the concept of homo religious—“religious man.” Finally, Carlson's work explains why these efforts—at times rich in hope and prospects—ultimately failed, often with tragic results. The tale inspires wistful regret over lost opportunities that, if seized, might have spared tens of millions of lives and forestalled or avoided the blights of fascism, Stalinism, socialism, and the advent of the servile state. And yet the book closes with hope, enunciating a set of principles that could be used today for invigorating a “family way” economy compatible with an authentic, healthy, and humane culture of enterprise.
Keywords: business & economics; economic history; economic theory; economics / comparative; history - modern; history / 20th Century

Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Keywords: countermovement; globalization; political economy; political science

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

Ancient Athens & modern ideology: value, theory & evidence in historical sciences : Max Weber, Karl Polanyi & Moses Finley - Nafissi, Mohammad (Institute of Classical Studies, School of Advanced Study, University of London, 2005)
Keywords: Athens (Greece); WEBER, Max, 1864-1920; civilization; classical civilization; classical philology; economic theory; economics; history / ancient / Greece; social science / sociology / general

Meat for the Multitudes: Market Culture in Paris, New York City, and Mexico City over the Long Nineteenth Century - Horowitz, Roger; Pilcher, Jeffrey M.; Watts, Sydney (American Historical Review, 2004)
Examines an earlier period of oscillation between state intervention and market liberalization in the meat trades of Paris, France New York City, and Mexico City, Mexico. Explanation on market culture; Argument of economic historian Karl Polanyi on the modern capitalist system and market rationality; Discussion on the rules governing the relationship between civil society and state power in the meat trade.
Keywords: Mexico; Mexico City; New York; Paris (France); civil society; intervention (federal government); liberalism; market liberalization; meat industry; state intervention

Debt Peonage in Granada, Nicaragua, 1870-1930: Labor in a Noncapitalist Transition - Dore, Elizabeth (Hispanic American Historical Review, 2003)
Revisits the debt peonage debate, central to understanding Latin American transitions to capitalism, particularly in Diormo, Granada, Nicaragua. Differences between capitalist and noncapitalist societies according to Karl Polanyi and Robert Brenner; Land peasantry in Diriomo; Legislation enacted to compel peasants to work in plantation agriculture.
Keywords: BRENNER, Robert, 1943-; Nicaragua; capitalism; debates and debating; history; labor laws & legislation; labour laws & legislation; peasants

The Forgotten Institution - Cangiani, Michele (International Review of Sociology, 2003)
Presents views of scholar Karl Polanyi on economic integration. Views of Polanyi on modern capitalist society; Distinction between external, local and internal markets by Polanyi. The three forms of economic integration include reciprocity, redistribution, and exchange. The article discusses Polyani's book "The Great Transformation," the development of market economies, the self-regulating market, some of the writings of Max Weber, big businesses, the efficiency of the market system, and social engineering.
Keywords: Great Transformation, The (Book); WEBER, Max, 1864-1920; big business; capitalism; international economic integration; social engineering

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (2003)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Great Transformation, The (Book); capitalism; class; critique; nationalism

Karl Polanyi and the creation of the "market society" - Gootenberg, Paul (The other mirror : grand theory through the lens of Latin America (Edited by Centeno, Miguel Angel, López-Alves, Fernando)., 2001)
Keywords: Latin America; economic history; philosophy; politics and government; social sceinces

Naukratis: Trade in Archaic Greece - Möller, Astrid (Oxford University Press, 2000)
Archaic Naukratis was a busy trading place in the Western Delta of the Nile, renowned for its sanctuaries and courtesans, granting the Greeks access to Egyptian grain and luxury items. Now, more than one hundred years after the discovery and excavation of Naukratis, the author offers the first full-length analysis of the archaeology and archaic history of this important site. Although Naukratis always features in modern accounts of ancient Greek colonization, it was not a place where the Greeks could freely establish their own political and social organization--it was under the strict control of the Egyptian pharaoh and his officials. To understand the special status of Naukratis, the author takes the port of trade model, surveying the political, social, and economic background of both Late Period Egypt and archaic Greece. A major section of the book comprises an archaeological re-evaluation of the topography of archaic Naukratis and its material finds. The sanctuaries, archaic pottery styles, terracottas, faiences, statuettes, and other small finds are examined in the light of recent scholarship, and an in-depth study of the literary evidence is brought to bear on the archaeological material. This book comprises a significant contribution to our understanding of Graeco-Egyptian relations during the seventh and sixth centuries BC and also demonstrates that Polanyian economic theory can play an invaluable rï¿½le in the ongoing debate about the concepts best employed to analyse the ancient Greek economy.
Keywords: Ancient Egypt; business & economics; economic history; history

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU, Pierre, 1930-2002; ELIAS, Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior